Breast cancer screening behavior and its associated factors in female employees in South Khorasan - Zoya Tahergorabi; Mahyar Mohammadifard; Fatemeh Salmani; Mitra Moodi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Breast cancer is a preventable disease, using three secondary preventive methods of mammography, clinical breast examination (CBE), and breast self-examination (BSE) that can lead to early detection of breast cancer. This study was designed to assess breast cancer screening behavior and its associated factors in females employed in South Khorasan. MATERIALS AND METHODS: In this analytic-descriptive study, 2256 female personnel of governmental organizations were investigated in Birjand city in 2016-2017. The data collection tool was a three-part questionnaire: sociodemographic characteristics, knowledge about breast cancer screening methods plus women's performance, and stage of change regarding screening behaviors of mammography, CBE, and BSE. The data were analyzed by SPSS 16 and one-way analysis variance, Tukey's post hoc, and multiple logistic regression model statistical tests. RESULTS: The mean ± standard deviation score of knowledge of the women was 3.45 ± 1.5. There was a significant difference of the mean score of knowledge between the single and married (P = 0.03) and age group (P = 0.04). The stage action of mammography, CBE, and BSE was 6.8%, 12.3%, and 16.8%, respectively. Logistic regression model showed that variables such as age and family history of breast cancer were highly significant related to mammography and also CBE. Knowledge was also highly significant in mammography, CBE, and BSE. Education level in CBE, marital status in BSE and mammography, and job in BSE were also significant (P < 0.001). CONCLUSIONS: This study reveals insufficient knowledge of female workers about breast cancer and the negative influence of low knowledge on the practice of breast cancer screening behavior. Therefore, the establishment and maintenance of regular educational courses for female employees is essential.